Reasons for dropout in swimmers, differences between gender and age and intentions to return to competition - Monteiro, D. M.; Marinho, D. A.; Moutão, J. M.; Vitorino, A. P.; Antunes, R. N.; Cid, L. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: This study's main purpose was to analyze reasons for dropout in competitive swimmers and differences between gender and age groups. The influence of dropout on swimmers intentions to return to competition, invariance across gender and validation of Questionnaire of Reasons for Attrition were also analyzed.